How city’s biggest employers shape spatial development of the residential areas – evidence from Olsztyn, Poland - Źróbek-Różańska, Alina; Źróbek, Sabina (International Conference “Environmental Engineering”, 2017)
Efficient managing sustainable urban development requires constant observations of trends in the key areas. One of the important areas is undoubtedly directing development of residential areas within the city and its surroundings. Nowadays, increasing incomes and transport mobility of the city citizens enable choosing between living within the city’s borders and building houses in the suburbs. Latter option makes city less compact and generates urban sprawl. As many controversies still arise over sprawling cities, the opposite of the smart growth, the factors behind this process should be monitored. In this article, we focused on spatial dependencies between localization of working and living places, because an access to the workplace seems to be one of the key determinants of choosing the particular place of residence. Therefore we decided to verify the following hypothesis: localization of the biggest employers in the city shapes the development of residential areas in the suburbs, and the influence depends on: current migration trends, specifics of the employers and their activity on the real estate market. The verification was carried out in the city of Olsztyn (Poland), the capital of Warmia and Mazury Province, and included careful analysis of the three city's biggest employers.
Keywords: urban sprawl; suburban areas; commuting